BERVE/LARGO, DEL FOLLETÍN A DOS CUENTOS DE MAUPASSANT - Rajoy Feijoo, María Dolores (Anales de Filología Francesa, 2007)
We know that popular newspaper serials is a genre which’s main characteristic is being published by instalments on newspapers or magazines, so its format ought to be long, at least as a conventional novel. This aspect of size cannot be reproduced on the brief tales of Maupassant, but other elements can. About its publication mode there is a first similarity, which consists in that both the tales and the newspaper serials were publicized on periodical press. About the content, newspaper serials usually reproduce pre-existent motives in literature already transformed in stereotype. We were struck about how close is a Maupassant tale, L’Enfant, with the newspaper serials ant the popular literature for its content which takes as a base the “natural son” motif. We analyze the relations of this work with the romantic newspaper serials and with the sentimental novel. We also go to see as a contrast other tale of the same author, La confession, which is already the same theme, the illegitimate son had with a lower, in a darkier way, and more approximate to fantastic or terror tales, but which also contains stereotypes from the popular literature. We search, as a conclusion, an explanation of similarities and differences between both genres.